Peak travel, peak car and the future of mobility: Evidence, unresolved issues, policy implications, and a research agenda - Phil Goodwin (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
In many advanced economies, car use per head, and sometimes total car traffic, has shown low growth. In some countries (and especially cities) it has declined. In a few countries, there have been similar studies of the distance travelled by all modes added together, which has shown a similar trend though with some doubts about how international air travel should be handled. It is generally agreed that the trends in the last few years must be influenced by world economic problems, but some of the possible changes in trend seem to go back ten or twenty years, with signs detectable even longer. Although there are differences of emphasis, the statistical facts of a reduction in historic growth, low growth or stability at national level, and reductions in specific locations especially some larger urban areas seem broadly agreed by most analyses. This evidence is sometimes ignored, but it is not contested. There is great interest in the appearance of some common features in many countries, notably including changes in the propensity to get driving licenses among young adults (especially teenage men), an apparent weakening of the association between income and mobility, a greater influence of public transport, walking and cycling to economic prosperity in some of the most successful cities, and the development of e-commerce, telecommuting, and social networks. There are currently differences in judgement on how influential these factors are, and on whether the observed trends are temporary, or reflect structural shifts which could be long-lived. These differences especially focus on the relative importance of economic issues (particularly prices and incomes), and wider social and cultural changes such as mobile internet access, demographic, gender, attitudinal and cultural trends, the effects of transport policies, and the possibilities of deeper concepts of `saturation' of mobility when further increases bring little extra benefit. There is at the moment no strongly established common view about future growth in car use to the extent that was taken for granted in earlier decades. The paper discusses research needs, and some emerging issues for future transport policies, including the appraisal of large scale transport infrastructure projects, service provision, pricing, the allocation of risk, and initiatives to reduce car dependence, in the context where forecasts are problematic and contested.
Keywords: 330